Assessment of Polypharmacy among Diabetic Patients in Tertiary Care Hospital of Nepal - Yadav, Anita; Acharya, Sagar; Chhetri, Pradip; Palikhey, Anjan (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Diabetes mellitus is a long-term metabolic condition that is accompanied by co-morbidities. Patients therefore use anti-diabetic medications in addition to other medications. Treatment with numerous drugs involves many hazards in addition to effectiveness. Therefore, diabetic people use multiple medications. The main aims of this study were to find out the prevalence of polypharmacy and the factors responsible for polypharmacy, and the consequences of polypharmacy. Material and Methods: A prospective observational study was conducted at the outpatient department of the Universal College of Medical Sciences and Teaching Hospital, Bhairahawa, Nepal from 12th February to 31st March 2021. A total of 150 patients who met the inclusion criteria and agreed to give written informed consent were enrolled in this study. A pre-validated questionnaire was used to assess polypharmacy among diabetic patients. The Statistical Package for Social Sciences (SPSS) software version 20 was used to enter and analyze data. Results: A total of 150 diabetic patients were included in this study. Among them, about 62.66% had polypharmacy. Age and duration of disease were highly significant with polypharmacy. Coexisting chronic conditions were highly associated with polypharmacy, like cardiovascular (AOR=5.552), musculoskeletal (AOR=5.050), mental (AOR=7.835), and digestive (AOR=3.778). The most common oral anti-diabetic agent was metformin. Conclusion: Polypharmacy was highly prevalent among diabetic patients. The rate of polypharmacy increases as the age and duration of disease increases. Polypharmacy has many consequences, like adverse drug events, increased costs, decreased compliance, and decreased quality of life.